POLITIK HUKUM KELUARGA ISLAM DI TUNISIA - Ismail Marzuki; Lathifah Munawaroh (Al-'Adl, 2019)
This paper discusses political Islamic family law in Tunisia. The stretch of political Islamic family law in Tunisia was seen after they were separated from the Ottoman Turks. Some Tunisian jurists think of making a legal codification based on Maliki madzhab. Besides that political domination by the Ottoman Turks and France has given color to the legal culture in Tunisia, even further influencing its laws. This paper shows several things: First is that Tunisia in carrying out its family's legal politics was influenced by Maliki and Hanafi madzhab (intra-doctrinal reform).Second, the political Islamic family law in Tunisia also contains rules that are not found in the Sunni madzhab (extra-doctrinal reform). Third, the political Islamic family law in Tunisia also uses a pattern of amendments and modifications to laws (regulatory reform). Fourth, Tunisia also conducts the codification that can be seen from the effort to codify Islamic law in al-Majallah fil Ahwal al-Syakhsiyyah lil Jumhuriyyah al-Tunisiyyah.